New entry proposal in a dictionary: A case study for the entry lotus - Hermina Sutami; Su Xinchun; Fransiska Wiratikusuma (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
New entry proposal in a dictionary: A case study for the entry lotusThe object of this study is the word lotus. In the Comprehensive Indonesian Dictionary (KBBI), the lotus entry has only one meaning within the botanical domain. However, the word lotus is also present and used in the context of Buddhism in Indonesia. Based on this fact, it is suggested to add a new meaning to the entry. The problem is to decide whether the new meaning is a polysemy or a homonym, and the criteria used to determine this.  The purpose of this research is to provide input to the Language Development and Fostering Agency to add new word entries to the KBBI using a case study of the word 'lotus' entry. Our research results on the word 'lotus' can expand the knowledge of the Indonesian people from the domain of botany to the domain of religion. In order to determine whether the entry is a polysemy or a homonym is carried out through Peirce's semiotic theory developed by Ogden and Richards to examine the relationship between three components that make up the word lotus as a sign. The research method involves analyzing the difference between the basic meaning and the new meaning, whether there is a development of a new meaning or a completely different meaning from the basic meaning. Unlike the previous studies, this research views meaning as a sign component. The lotus entry is a sign consisting of symbol, thought or reference, and reference components.Proposal entri baru dalam kamus: Studi kasus untuk entri terataiObjek penelitian ini adalah kata teratai. Dalam Kamus Besar Bahasa Indonesia (KBBI), entri teratai hanya memiliki satu arti dalam domain botani. Namun, kata teratai juga hadir dan digunakan dalam konteks agama Buddha di Indonesia. Berdasarkan fakta ini, disarankan untuk menambahkan arti baru. Persoalannya adalah apakah makna baru tersebut merupakan polisemi atau homonim, dan kriteria apa yang digunakan untuk menentukan entri sebagai polisemi atau homonim. Tujuan dari penelitian ini adalah untuk memberikan masukan kepada Badan Pengembangan dan Pembinaan Bahasa untuk menambahkan entri kata baru untuk KBBI dengan menggunakan studi kasus dari entri kata teratai. Hasil penelitian dari kata teratai dalam studi ini dapat memperluas pengetahuan masyarakat Indonesia dari ranah botani ke ranah religi. Penentuan bahwa kata ini merupakan sebuah polisemi atau homonim dilakukan melalui teori semiotika Peirce yang dikembangkan oleh Ogden dan Richards untuk mengkaji hubungan antara tiga komponen yang membentuk kata teratai sebagai tanda. Metode penelitian ini melibatkan analisis perbedaan antara makna dasar dan makna baru, apakah ada pengembangan makna baru atau makna yang sama sekali berbeda dari makna dasar. Berbeda dengan penelitian sebelumnya, penelitian ini memandang makna sebagai komponen tanda. Entri teratai adalah tanda yang terdiri dari simbol, pemikiran atau referensi, dan komponen referensi.